Grabar la alteridad: Transferencias y mediaciones técnicas en la antropología mexicana. - Lira, Regina (Studies in Latin American Popular Culture, 2019)
Based on historical documents, press, museum collections, and academic publications, the early introduction of the phonograph in Mexico and its late incorporation into anthropology is the starting point to reconstruct the Mexican and American network cobuilt by this technology and the symmetrical and asymmetrical relational modes it helped reproduce and extend that built their respective social-science programs. We will address the question of why a technology is successful in one place and a failure in another through the reconstruction of the early attempts of the phonograph's transference to Mexico during the last decades of the nineteenth century and the process of its stabilization in Mexican anthropology until the 1940s. Based on Latour's technical mediation approach, the agentive role of this technological object renders visible the internal conflicts and intellectual traditions that assigned a specific role to Amerindian societies in Mexican anthropology, thus confronting the universal ambitions of the scientific program designed by the agents engaged in the process.